Biologic remodeling of periodontal dimensions of areas treated with gingival augmentation procedure: A 25-year follow-up observation (2020)
Background: The role of keratinized tissue (KT) for maintenance of periodontal health has been debated for many years. This study assesses the long‐term “biologic remodeling” of periodontal dimensions of teeth treated with free gingival grafts (FGGs) compared with adjacent/untreated teeth. Methods: Seventy‐four patients with at least one site showing absence or a reduced amount of attached gingiva associated with gingival recession (GR) at baseline were treated with FGGs in a private practice. Patient/tooth/site‐associated variables were recorded for each patient (treated and mesial/distal adjacent teeth) at baseline (T0), 6 months after surgery (T1), during the follow up period (T2) (mean 15.3 years), and at the end of the follow‐up period (T3) over 25 years. Parametric, non‐parametric, and mixed effects logistic regression statistics were used throughout the study. Results: A total of 182 teeth submitted to FGGs were compared with 247 untreated/adjacent teeth. The majority of treated teeth (n = 152; 83.5%) showed GR depth (GRD) reduction (P <0.001). Conversely, untreated/adjacent teeth displayed GRD increase at T3 (P <0.001). Statistically significant KT band contraction was also found at treated sites, whereas adjacent sites presented small clinical improvements (P <0.001). The total root‐coverage esthetic score of the areas including treated and adjacent untreated teeth improved from T2 to T3 (P <0.001). Some independent variables, such as age, tooth type, and GRD at T1 seem to influence GRD and KT changes over time. Conclusions: Soft tissue augmentation procedures may modify the biologic remodeling of periodontal dimensions over time associated with aging. Use of FGGs may promote more favorable KT dimensions and improve marginal tissue recession.